THE CHALLENGES OF FAMILY EDUCATION IN DEVELOPING 21ST-CENTURY SKILLS AND CHARACTER VALUES AMONG YOUTH - Suardi; Muhammad Asri; Sitti Fatimah Achmad; Asmar; Ryan Rayhana Sofyan (LLDIKTI Wilayah X, 2024)
This study aims to understand the challenges faced by families in instilling character and supporting the development of 21st-century skills among youth. Using a descriptive quantitative approach, respondents were parents with children enrolled in secondary schools or equivalent in Maros Regency, South Sulawesi. The findings indicate that families have not yet fully optimized their role as primary supporters in building a young generation ready to face global challenges. Difficulties in supporting digital skills, a lack of role models at home, and negative influences from external factors such as social media are key issues. Families struggle to provide opportunities for relevant skill training, leading to low readiness among youth to compete in the era of globalization. This study underscores the importance of improving family literacy in character education and 21st-century skills. Practical training-based interventions for families and policies that enhance access to training, along with strengthened synergy between families, schools, and communities, are identified as strategic solutions.